Islamic financial literacy in the digital era to encourage the realization of financial well-being among Generation Z students in Kudus - Ibnu Muttaqin; Irsad Andriyanto; Rendy Firmansah; Jadzil Baihaqi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This Community Service (PkM) activity aims to enhance the understanding of digital financial management among Islamic boarding school students (santri) in a prudent manner and in accordance with sharia principles. The initiative is motivated by the rising cases of online loan misuse and online gambling among the younger generation, including santri, due to a lack of digital financial literacy. With 73 participants and several stakeholders, the program was designed using a Learning Service methodology. The material was delivered through a practical approach supported by real-life case studies. The evaluation results demonstrated a significant improvement in participants’ understanding, as evidenced by an increase in the average test scores from 74 in the pre-test to 94 in the post-test, representing a 20 per cent gain.. This finding highlights the effectiveness of the workshop in delivering in-depth and applicable insights to participants. The positive impact of the activity extended beyond improved understanding, fostering awareness of the risks associated with irresponsible use of financial technology.The outcomes of this program underscore the value of collaborative efforts among various stakeholders to develop educational initiatives that are both impactful and relevant in addressing the challenges posed by the digital era